Rumensin®-Tylan® combinations in limit-fed growing diets: effects on growing and finishing performance and carcass characteristics - Sean P. Montgomery; T.B. Farran; J.J. Sindt; C.M. Coetzer; J.N. Pike; A.M. Trater; H.J. LaBrune; R.D. Hunter; S.B. Laudert; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2001)
Five hundred seventy-two crossbred beef heifers were used to compare gain and feed efficiency of cattle consuming restricted quantities of energy-dense growing diets containing varying concentrations of Rumensin® and Tylan®. Growing treatments consisted of providing Rumensin at 30 grams per ton of dry matter (R30), or 250 mg per head per day (R250). A third treatment consisted of a Rumensin/Tylan combination, providing 250 and 90 mg per head per day of Rumensin and Tylan, respectively (R250/T90). Average daily gain and feed efficiency during the growing phase were not different (P>0.90) among treatments. Heifers that received R250/T90 during the growing phase exhibited lower dry matter intakes (P0.50), R250/T90 increased finishing-phase feed efficiency by 6.1 and 3.5% compared to R30 and R250, respectively. Liver abscesses were lower (P<0.10) for R250/T90 and R30 than R250.
Keywords: Cattlemen' s Day; 2001; Kansas Agricultural Experiment Station contribution; no. 01-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 873; Beef; Rumensin; Tylan; Limit feeding